Da (in)aplicabilidade do princípio do não confisco às multas tributárias: uma análise da jurisprudência do Supremo Tribunal Federal - Barros, Thiago Maciel Pinheiro (2021)
This dissertation aims to discuss the limits of tax sanctions in the brazilian legal system. It employs the deductive method to carry out a qualitative and exploratory research, making use of bibliographical analysis of the brazilian doctrine and documental analysis based on legislative documents and judicial decisions. It understands that he logical-semantic constricuvism is a theoretical-methodological lens for understanding contemporary legal phenomena. It identifies that the concept of sanction is linked to an essential element of law and that it forms the sanctionatory legal relationship. It understands that the sanctions in the tax law have the tax infraction as a antecedent and are manifested in the form of punitive and sanctioning fines. It sees that the limits for the institution of tax sanctions are set by the Federal Constitution based on constitutional principles. It understands that the jurisprudence of the Federal Supreme Court, despite the plurality of cases, continues to safeguard the constitutional text by imposing limits on the institution of fines that violate the Federal Constitution